Teacher Strategies in Multicultural Citizenship Education - Pitri Ayu (International Journal of Students Education, 2024)
This research aims to find out what teachers’ strategies are in multicultural citizenship education. The research method used in this article is a systematic literature review. The author searches for journals that have been published on Google Scholar which relate to the research title or topic that the researcher has determined. The articles searched are limited to as many as Then the researchers filtered 8 articles into 3 articles that were considered appropriate and related to the research topic. The results of the research show that as many as 3 articles from the search results can be identified what teacher strategies are in multicultural citizenship education. So the conclusion from the research results shows that teacher strategies in multicultural citizenship education can be done in various ways, including through curriculum development, through student development programs, and also through several methods such as Cooperative Learning, Inquiry Learning Approach, Active Learning, Teaching in Differentiation, and Interdisciplinary Unit Programme.